Morphological development of lily (Lilium ‘Siberia’) floral organs - Zheng-Yao, Zhang; Xiao-Feng, Liu; Chang-Wei, Zhao; Xin-yu, Lyu; Wan-qing, Li; Wen, Sun; Pin-San, Xu (Bangladesh Journal of Botany, 2019)
Effects of flower buds of oriental lily “Siberia”, Asian Lily “Desert Storm” and “Shuttle Red” on the growth and development during different developmental stages of plants were investigated. The results showed that the plant height of different lily was not different in different periods, and the growth increased rapidly during seeding stage to squaring period while slowly in the squaring period to full-bloom stage. The size of flower organs was different, the "Siberia" was significantly larger than "desert storm" and "shuttle red", and the development of ovary and anther was earlier. The intraepidermal of epidermal cells of lily petals were smaller than those of outer epidermal cells. The number of intraepidermal cells is much more higher than the number of outer epithelial cells. The infiltration degree of lily petals was related to the growth of intraepidermal and outer epidermal cells of petals. The growth rate of intraepidermal cells in "Siberia" was significantly higher than that in outer epidermal. The growth rate of intraepidermal cells in "desert storm" and "shuttle red" was slightly higher than that of outer epidermal, which proved that the uneven growth of petals of intraepidermal and outer epidermal cells leads to lily petals’ bent, thereby results in the formation of different flower types.